2019
DOI: 10.1155/2019/4262013
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Water Relations of Two Contrasting Date Palm Genotypes under Salinity

Abstract: Salinity is a global agricultural problem, resulting in a significant reduction in the plantation areas and the crop yields, especially in arid and semiarid regions. The date palm is relatively salt-tolerant plant species, although the nature of salt tolerance is poorly understood. In this study, the salt stress responses of a salt-tolerant “Umsila” was compared with salt-susceptible “Zabad” date palm cultivars. Various physiological parameters, plant-water relations, and anatomical characteristics were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 99 publications
4
23
1
Order By: Relevance
“…5), suggesting that free amino acids were more important as osmolytes than sugars (Hartzendorf & Rolletschek, 2001). However, salt induced accumulations of proline (Djibril et al, 2005;Yaish, 2015;Al Kharusi et al, 2019a) were not observed in the current study, probably due to the intraspecific variations of date palm (Al Kharusi et al, 2019a,b), as well as a counteraction of flooding as reported in several other species, for example cabbage palm (Williams, 1996), Juncus kraussii (Naidoo & Kift, 2006). Much stronger accumulation of amino acids were Asterisks indicate significant differences at: *, P < 0.05; **, P < 0.01; ***, P < 0.001; respectively, between the seawater flooding and control treatments examined using Student's t-test (n = 5-6).…”
Section: Compatible Solutes and Root-shoot Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…5), suggesting that free amino acids were more important as osmolytes than sugars (Hartzendorf & Rolletschek, 2001). However, salt induced accumulations of proline (Djibril et al, 2005;Yaish, 2015;Al Kharusi et al, 2019a) were not observed in the current study, probably due to the intraspecific variations of date palm (Al Kharusi et al, 2019a,b), as well as a counteraction of flooding as reported in several other species, for example cabbage palm (Williams, 1996), Juncus kraussii (Naidoo & Kift, 2006). Much stronger accumulation of amino acids were Asterisks indicate significant differences at: *, P < 0.05; **, P < 0.01; ***, P < 0.001; respectively, between the seawater flooding and control treatments examined using Student's t-test (n = 5-6).…”
Section: Compatible Solutes and Root-shoot Interactionsmentioning
confidence: 99%
“…Although date palms are thought to be a salt‐tolerant crop able to grow in soils up to 12 dS m –1 without showing symptoms of salt stress (Ramoliya & Pandey, 2003; Yaish & Kumar, 2015; Patankar et al ., 2019; Al‐Harrasi et al ., 2020), salinity can lead to significant economic losses in date palms (Tripler et al ., 2011; Yaish & Kumar, 2015; Al‐Muaini et al ., 2019). This is particularly observed in salt susceptible cultivars (Al Kharusi et al ., 2017, 2019a; Hazzouri et al ., 2020), which showed significantly declined photosynthesis, shoot and root growth and foliar water content under salt stress (Alhammadi & Edward, 2009; Al Kharusi et al ., 2017). Salt stress affects their growth and productivity independently of drought and heat (Alhammadi & Kurup, 2012), and constitutes an increasing problem in date palm plantations due to irrigation and fertilisation.…”
Section: Introductionmentioning
confidence: 99%
“…Al Kharusi et al (2019b) studied the seedling offspring of a salt tolerant variety, 'Umsila, ' and salt sensitive variety, 'Zabad.' They reported that salt tolerant seedlings responded to salinity by developing a thicker protective Casparian strip in roots, increasing osmolyte and compatible solute concentrations including proline, glycine betaine, and total sugar.…”
Section: Salinity Salinity Tolerance In Date Palmsmentioning
confidence: 99%
“…Until present time, exceptionally powerful control measures have yet to be found. Sadly, that creepy crawly bug type, the red palm weevil, is the starting point from tropical South Asian (Al- Kharusi et al, 2019). Moreover, the illnesses are also caused essentially by parasites and phytoplasma, for example, deadly yellowing and Bayoud Fusarium shrink, which are the danger to the date palm in Malaysia.…”
Section: Insect Pest Attackmentioning
confidence: 99%
“…Despite large volume of date import every year, Malaysia also produces local dates in small scale farm concept. Unfortunately, these smallholder farmers lack of knowledge and information about standard farm management of dates, resulting in poor farm production practice and methods (Young, 2010, Al-Kharusi et al, 2019. Hence, the presence of small scale farming with low production of dates can be seen as such a potential matter to improve this sector.…”
Section: Introductionmentioning
confidence: 99%